Rapid Investigation and Screening of Bioactive Components in Simo Decoction via LC-Q-TOF-MS and UF-HPLC-MD Methods - Yingjie He; Pi Cheng; Wei Wang; Sien Yan; Qi Tang; Dongbo Liu; Hongqi Xie (Molecules, 2018)
Simo decoction (SMD), as a traditional medicine, is widely used in the treatment of gastrointestinal dysmotility in China. In this study, a combined method of liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS) and ultrafiltration high-performance liquid chromatography molecular docking (UF-HPLC-MD) was efficiently employed to identify and screen bioactive ingredients in SMD. Ninety-four major constituents were identified or tentatively characterized by comparing their retention times and mass spectra with standards or literature data by using LC-Q-TOF-MS, and the ascription of those compounds were classified for the first time. Among them, 13 bioactive ingredients, including norisoboldine, eriocitrin, neoeriocitrin, narirutin, hesperidin, naringin, neohesperidin, hesperitin-7-O-glucoside, linderane, poncirin, costunolide, nobiletin, and tangeretin, were primarily identified as the human serum albumin (HSA) ligands at a range of docking scores from −29.7 to −40.6 kJ/mol by UF-HPLC-MD. The results indicate the systematic identification and screening of HSA ligands from Simo decoction guided by LC-Q-TOF-MS and UF-HPLC-MD represents a feasible and efficient method that could be extended for the identification and screening of other bioactive ingredients from natural medicines.